PERFORMANCE OF MASONRY BRICK WITH CALCIUM HYDROXIDE AS MORTAR - Darmono Darmono; Slamet Widodo; Maris Setyo Nugroho; Faqih Ma’arif (Jurnal Pensil : Pendidikan Teknik Sipil, 2023)
This study aims to determine the shear strength and flexural strength of red brick masonry, determine the effective thickness of calcium hydroxide mortar with a mixture ratio of 1Kp:2Ps, and determine the failure pattern of red brick masonry due to the load received during the direct shear strength test and flexural strength test. The research was conducted by experimental method. The tests carried out were the direct shear and flexural strength tests. Variation of successive mortar thickness of 10mm, 15mm, and 20mm. The test object is 18 (eighteen), the thickness variation consists of 3 test objects. Data analysis used descriptive quantitative by finding the average value of the shear strength and flexural strength. Based on the test results, the average compressive strength and splitting tensile strength of the mortar were 0.613 MPa, 0.0414 MPa. The average shear strength with a 10mm; 15mm; and 20mm is 0.025 MPa; 0.020 MPa; and 0.016 MPa, respectively. The flexural strength of mortar thickness with 10mm, 15mm, and 20mm are 0.034 MPa; 0.045 MPa; and 0.041 MPa, , respectively. In the masonry shear test, the effective thickness of the mortar was found at 10mm with a maximum shear strength of 0.025 MPa, while in the flexural test, the effective thickness of the mortar was found at a thickness of 15mm with 0.045 MPa. The pattern of failure in red masonry's shear strength and flexural strength tests is the mortar failure.